AN ANALYSIS OF DETERMINANTS OF PATIENT PREFERENCES IN OUTPATIENT SERVICES AT HOSPITAL ROYAL PRIMA MARELAN - Fifi Achwani; Ermi Girsang; Sri Lestari Ramadhani Nasution (Jurnal Scientia, 2023)
Intense competition in the health care market requires hospitals to be able to emphasize their advantages over their competitors. Previous studies have shown that patients demand more choice in the health care they receive. Previous research has shown that patient preferences influence patients' willingness to use health care services at a hospital. This study aims to analyze the factors that contribute to patient preferences in outpatient services. The research design used in this study was analytic descriptive non-experimental research with a cross sectional approach. The research was conducted at Royal Prima Marelan Hospital from November 2022 to January 2023. The sample in this study was 381 outpatients. Samples in this study were selected using accidental sampling method. From the Chi Square test results, it is known that education (p=0.714) and income (p=0.430) are not statistically significantly related to patient preferences for outpatient services. Whereas ownership of health insurance (p=0.045), distance (p=0.002), and patient perception (p=0.000) were statistically significantly related. From the results of the logistic regression test, it can be concluded that patient perception is the variable that most influences patient preferences for outpatient services. With an Exp(B) value of 3.739 (95%CI 2.301-6.077), respondents who have unfavorable patient perceptions are 3.7 times likely not to reuse outpatient services.